Perilaku Masyrakat dalam Menjaga Kebersihan Lingkungan Objek Wisata Jembatan Akar di Kecamatan Bayang Pesisir Selatan - Sari, Mega Permata (Pendidikan Geografi, 2014)
This study aims to determine the behavior of the community in keeping the environment cleanattraction root bridge . The problem in this study are : 1 ) Community Behavior in theEnvironment Keeping Attractions dikecamatan Shaded Bridge Aka the South Coast .2 ) Management of Environmental hygiene Attractions Root Bridge in the district of SouthCoastal shadow .This type of research is qualitative research . Determination of informants obtained by purposivesampling technique . The research location is in kenagaraian Puluik - Puluik subdistrict of NorthBayang . Informants in this study is the head of the Department of Tourism and Culture , Head ,manager of Community Leaders and Visitor Attractions . Data collection techniques used wereobservation, interviews , and written documentation .Based on the results of field research shows that environmental hygiene Attractions Root BridgeKebersihanya not awake much garbage strewn on the location , attractions Root Bridge has theattraction that the bridge is made from the roots of the banyan are formed by the local society .Governments have to enter into the profile Attractions Attractions region , and the government hasalso been promoting the attractions through the mass media . People are also often hold mutualhelp to clean the environment Attractions Root Bridge .